2009
DOI: 10.1111/j.1365-2516.2009.02005.x
|View full text |Cite
|
Sign up to set email alerts
|

Factor VIII and von Willebrand factor interaction: biological, clinical and therapeutic importance

Abstract: Summary. The interaction of factor VIII (FVIII) with von Willebrand Factor (VWF) is of direct clinical significance in the diagnosis and treatment of patients with haemophilia A and von Willebrand disease (VWD). A normal haemostatic response to vascular injury requires both FVIII and VWF. It is well-established that in addition to its role in mediating platelet to platelet and platelet to matrix binding, VWF has a direct role in thrombin and fibrin generation by acting as a carrier molecule for the cofactor FV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
141
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(145 citation statements)
references
References 118 publications
0
141
0
4
Order By: Relevance
“…20 Second, VWF acts as a carrier molecule for procoagulant factor (F) VIII, thereby protecting it from premature proteolytic degradation and clearance. 22 VWF synthesized within ECs is either constitutively secreted into the plasma or, alternatively, stored within intracellular organelles known as Weibel-Palade (WP) bodies. 23,24 This stored VWF is enriched in high-molecular-weight multimers and is secreted together with other WP contents following EC activation.…”
Section: Vwf In Malariamentioning
confidence: 99%
“…20 Second, VWF acts as a carrier molecule for procoagulant factor (F) VIII, thereby protecting it from premature proteolytic degradation and clearance. 22 VWF synthesized within ECs is either constitutively secreted into the plasma or, alternatively, stored within intracellular organelles known as Weibel-Palade (WP) bodies. 23,24 This stored VWF is enriched in high-molecular-weight multimers and is secreted together with other WP contents following EC activation.…”
Section: Vwf In Malariamentioning
confidence: 99%
“…This requires sound knowledge of cell types capable of replacing FVIII, especially within proximity of von Willebrand factor (vWF), which protects FVIII from degradation. 2 However, the cell-type origin of FVIII has been controversial. 3 Correction of hemophilia after orthotopic liver transplantation (OLT) but not after kidney transplantation, despite FVIII mRNA expression in both organs, 3,4 indicated that liver was a major site for FVIII production.…”
Section: Introductionmentioning
confidence: 99%
“…Von Willebrand factor (vWF) is a multimeric glycoprotein produced by the vascular endothelium and megakaryocytes that is crucial for hemostasis, and functions as a carrier protein for factor VIII (FVIII) and as a bridge between the subendothelial matrix and platelets (4). The distinctive properties of the distinct molecular masses of VWF influence its ability to mediate platelet adhesion and aggregation (5).…”
Section: Introductionmentioning
confidence: 99%